Adsorption induced magnetic anisotropy in the two-dimensional magnet CrCl3. (November 2020) - Luo, M.; Li, Y.D.; Wang, K.J.; Shen, Y.H.
Abstract: Two-dimensional (2D) CrCl3 has attracted much attention as it is reported to be a ferromagnetic semiconductor. By performing first-principles calculations, we investigate the effects of Li and F adsorption on the saturation magnetization and magnetic anisotropy energy (MAE) of CrCl3. It is observed that Li adsorption can dramatically enhance its saturation magnetization, and tune its easy magnetization axis to the in-plane direction from original out-of-plane. The monotonic enhancement of in-plane magnetism in CrCl3 as the coverage of Li increases are attributed to electrostatic doping induced by charge transfer between Li atoms and Br atoms. By contrast, the F adsorption reduces the out-of-plane magnetism in CrCl3 as the coverage of F increases but keeps the original easy magnetization. These findings will benefit for further understanding of the tunable magnetic properties of CrCl3 and push 2D spintronics applications. Highlights: The magnetism of CrCl3 monolayer becomes remarkably tunable by charge doping based on density functional calculations. Li adsorption significantly enhances magnetic anisotropy energy (MAE) of CrCl3 monolayer as electron doping. F adsorption can also enhance MAE as hole doping but distorting the CrCl3 . Li adsorption can also tune the easy axis of CrCl3 from out-of-plane to in-plane.